Peningkatan Kemampuan Guru Menyusun RKH Bermuatan Pendidikan Karakter Melalui Metode Pembelajaran Partisipatif - Putri Larasati Ayuningtyas (Universitas Trunojoyo Madura, 2014)
This study aims to determine whether there is an increase in the ability of teachers to draft the daily activities laden character education through participatory learning methods. Teacher‟s ability to draft the daily activities of the charged character is a teacher who developed the character values of the nation on self-learners.learning methods modified using contextual learning approach to develop character. Revised assessment expressed qualitatively. Participatory learning method is a method of learning which can encourage students to contribute and engage actively and independently in acquiring the knowledge and skill learned. This study used an experimental design with pre-type experiments conducted on the subject of teacher research play group and TK. Reliability analysis shows the value of coefficient alpha 0,267, for the scale of teacher knowledge. While the value of Asymp, Sig (2-tailed) to ability of the teacher of 0,002 it can be concluded Ha acceptable and meaningful participatory learning methods to enhance the knowledge and ability of teachers to draft the daily activities charged character education. The results showed participatory learning methods can improve the ability of teachers in preparing the draft the daily activities charged character education. This is because in a participatory learning of participants involved in the process of preparing draft the daily activities charged character education, as well as the participants were eager and opens to the new knowledge.